La « femme·eux·ze » musique québécoise : La recherche sur les genres, les sexualités et autres pratiques non dominantes en musique au Québec (1874-2022) - Blais-Tremblay, Vanessa (Nouveaux cahiers de recherche, 2023)
C’est là un ouvrage de référence qui présente la recherche sur la musique, les genres et les sexualités, et plus largement la vie musicale non dominante au Québec depuis le dernier quart du XIXe siècle jusqu’à aujourd’hui. Issu des travaux réalisés en 202-2022 par le pôle universitaire DIG! Différences et inégalités de genre dans la musique au Québec (D!G), un réseau interdisciplinaire et intersectoriel qui réunit les chercheur·ses, publics, artistes et autres professionnel·les de la musique qui s’intéressent à cette thématique, l’ouvrage comprend une revue de la littérature et une bibliographie de plus de 800 ressources scientifiques.

De l’expression d’un désir gay et du queer dans l’opéra contemporain : le cas d’Elia (2004) de Silvio Palmieri - Champagne, Éric (Circuit: Musiques contemporaines, 2021)

Introduction. Parole queer et musiques contemporaines : vivre et créer hors de la norme - Champagne, Éric; Rhéaume, Martine (Circuit: Musiques contemporaines, 2021)

Queer Perspectives in New Music - Dharmoo, Gabriel; Brosin, Annette; R. Green, Anthony; Nickel, Luke; Doolittle, Emily; Henry, Symon; Kasahara 笠原 貞野, Teiya (Circuit: Musiques contemporaines, 2021)

Altérité et création : comment peut-on s'épanouir artistiquement dans la différence, au-delà des discours sur la diversité ? - Henry, Symon (Les Cahiers de la Société québécoise de recherche en musique, 2021)
Comment le fait d’être métis égypto-québécois·e influe-t-il sur ma manière de composer, d’écrire, de dessiner ? Et le fait d’être queer, neurodivergent·e, pauvre, ou encore d’avoir souffert de troubles de santé mentale ? Autrement formulé : comment, à partir d’une posture intersectionnelle, peut-on s’inscrire dans un cadre artistique donné et communiquer nos codes à un public qui ne les possède majoritairement pas ? Comment parler de ma voix propre, particulièrement minoritaire, afin d’éviter que d’autres s’approprient ma réalité ? Voilà les questions principales qui sont abordés dans cet article où je présente mon travail où partitions graphiques, poésie et arts visuels ont constitué le socle de ma démarche artistique au fil de plus d’une décennie de création. Pour y répondre, j’aborderai certains concepts-clés (intersectionnalité, tiers-espace, etc.) centraux dans ma réflexion, deux projets qui adressent de front ces questions et réalités, et, surtout, de nombreuses digressions proposant des bribes d’imaginaires les sous-tendant. Les projets abordés sont d’abord mon premier opéra, Le Désert mauve, d’après un texte éponyme de Nicole Brossard — chef-d’oeuvre des littératures lesbiennes, queers et québécoises. Puis le spectacle L’Outre-rêve et plus spécifiquement ma pièce L’amour des oiseaux moches, commande de l’Ensemble contemporain de Montréal (ECM+), où mes mots, ma musique et mes visuels donnent vie à quatre personnages imbus de réalisme magique (Djinn, Louve, Vieux Clown et Eunuque que j’aime) par l’entremise de pièces pour voix, scie musicale, accordéon et orchestre.

« Je ne m’apitoie plus sur le fait » : homosexualité et engagement identitaire dans les écrits et prises de parole de Claude Vivier - Rhéaume, Martine (Circuit: Musiques contemporaines, 2021)

Death and Fairy Tale: Queer Autothanatography in Claude Vivier - Kingston, Andrew (differences, 2020)

“Saw You in the Dark”: Exploring Rufus Wainwright’s Emotional Vulnerability in Fan-Captured Live Performance Videos - Salerno, Stephanie (Performance Matters, 2019)

La scène travestie qui est à l’origine du punk à Montréal - Desfossés, Félix B. (Vice, 2017)

Claude Vivier ou la machine désirante - Richard, Robert (Éditions Varia, 2017)
"Claude Vivier, compositeur méconnu au Québec, est né à Montréal en 1948. Il meurt assassiné à Paris en 1983. Il a fait ses études avec Gilles Tremblay et Karlheinz Stockhausen. Son œuvre -- qui contient une quarantaine de titres -- est inclassable, s'inspirant de ou bougeant à travers des époques très différentes de l'histoire de la musique, depuis le Moyen Âge jusqu'à la musique dite « spectrale » des années 1980. C'est une œuvre d'une grande originalité, qui a choisi la fuite hors des attentes ou des formes prévues et qui a cherché à délirer les continents, les langues, les peuples."--From publisher's website

Claude Vivier at the End - Goldman, Jonathan (Contemporary Music and Spirituality, 2016)

« La terre qui nous a vus grandir ». Le sujet et le monde chez Mara Tremblay, Ariane Moffatt et Salomé Leclerc - Pirie, Nathan (Université de Waterloo, 2016)
Cette étude inclut les œuvres de Mara Tremblay, Ariane Moffat et Salomé Leclerc et vise un objectif double : d’une part, il s’agit d’analyser des textes lyriques qui ont une indéniable qualité poétique et d’autre part, de réaliser une étude intermédiale alliant texte, musique et clip-vidéo afin de voir comment le sens d’un de ces éléments est infléchi, modifié ou complété par celui des autres éléments. L’hypothèse de recherche est qu’aujourd’hui, les auteurs-compositeurs-interprètes conçoivent leur art à travers trois langages esthétiques (le texte, la musique et la vidéo), faisant de la musique une expérience plurisensorielle et intermédiale. Pour faire émerger le message de ces artistes, on mobilisera les théories du care et l’écoféminisme afin d’analyser le discours portant sur le sujet et le monde. On vise à dégager les grands thèmes de ces œuvres à travers une synthèse de ces trois approches critiques. L’analyse du corpus vise à déterminer la qualité poétique des textes et la vision du monde que ces trois artistes diffusent.

True Loves, Dark Nights: Queer Performativity and Grieving Through Music in the Work of Rufus Wainwright - Salerno, Stephanie (Université d'État de Bowling Green, 2016)

Rufus Wainwright - Williams, Katherine (Equinox Publishing, 2016)
Canadian-American singer-songwriter Rufus Wainwright is famous around the world for his multi-faceted musical style, shown through both his recorded output and his engaging live performances. Katherine Williams combines aspects of his life story with scholarly readings drawn from several methodologies.

Rufus Wainwright sings "Grey Gardens": on Thomas Mann's "Death in Venice", Tadzio and his pop cultural "life" - Bałżewska, Katarzyna (Beyond Philology: An International Journal of Linguistics, Literary Studies and English Language Teaching, 2015)

L'esthétique rock queer : de C.R.A.Z.Y. à Xavier Dolan - Laverdière, Gabriel (Nouvelles vues. Revue sur les pratiques et les théories du cinéma au Québec, 2015)
L'analyse proposée des films C.R.A.Z.Y. (Jean-Marc Vallée, 2005), J'ai tué ma mère (Xavier Dolan, 2009), Les amours imaginaires (Dolan, 2010) et Laurence Anyways (Dolan, 2012) convoque trois perspectives : le rock, le camp et le queer. Dans ces films québécois, la musique rock semble orienter la narration et l'esthétique. Elle fait également le pont entre l'anticonformisme auquel renvoie le paradigme rock et l'identité marginale des personnages. L'esthétique de l'image se plie parfois à la bande sonore, qui encourage certains effets visuels. Cela dit, les films de Vallée et de Dolan se servent différemment de l'esthétique rock et du camp, ce qui s'accorde aux représentations distinctes qu'ils produisent eu égard à l'orientation ou à la diversité sexuelles et au genre. L'excès des films de Dolan, leur hyperréférentialité, leur jeu constant entre recherche d'émotions esthétiques et d'émois narratifs, leur fréquente suspension de la réalité contribuent à une écriture du différé dans laquelle les personnages queer jouissent d'une amplitude considérable, alors que dans C.R.A.Z.Y. la performance hyperbolique s'articule plutôt à une analytique de l'homophobie (sociétale et intériorisée) que le film s'efforce de dresser, sans pouvoir échapper à un certain malaise.

Vivier reenacted: Singing beyond masculine - Novak, Jelena (New Sound: International Magazine for Music, 2015)
Vivier: A Night Report is a kind of poetical archive of musical details, protocols, experiences, concepts, memories, fears, desires and sorrows connected to Canadian composer Claude Vivier's (1948-1983) unusual destiny. All characters from Marko Nikodijević's opera originate from Vivier's life and works but they are re-indexed, or reenacted differently. The countertenor voice of Vivier is what primarily makes him different from all the rest of the characters. Even it could be claimed that the rest of the voices are dominated by Vivier's vocal presence on stage. Vivier stands as symbol for minority, queer, vulnerable. During his short life he was trying to get his own voice, voice as the personification of freedom and possibility to be heard. Finally he gets vivid, imaginative opera in which both his physical and personified voices are shining by creativity that his art emanate. He gets his singing voice, and he finally gets heard.

Shock, glam, punk - Desfossés, Félix B. (No Speed Limit (1964-1989). L’évolution du métal québécois, 2014)

Michel Louvain. Sans âge - Gignac, Benoît (Éditions Caractère, 2014)
Découvert au milieu des années 50, admiré et adulé, Michel Louvain fait encore battre les coeurs près de 60 ans après avoir amorcé sa carrière. Ce livre-coffret retrace le parcours irréprochable de cet artiste accompli, qui a remporté les honneurs autant pour ses performances sur disque, sur scène et à la télévision que pour son soutien à des causes sociales.

Claude Vivier: A Composer’s Life - Gilmore, Bob (University of Rochester Press, 2014)
Claude Vivier's haunting and expressive music has captivated audiences around the world. But the French-Canadian composer is remembered also because of the dramatic circumstances of his death: he was found murdered in his Paris apartment at the age of thirty-four. Given unrestricted access to Vivier's archives and interviews with Vivier's family, teachers, friends, and colleagues, musicologist and biographer Bob Gilmore tells here the full story of Vivier's fascinating life, from his abandonment as a child in a Montreal orphanage to his posthumous acclaim as one of the leading composers of his generation. Expelled from a religious school at seventeen for "lack of maturity," Vivier gave up his ambition to join the priesthood to study composition. Between 1978 and 1981 Vivier wrote the works on which his reputation rests, including 'Lonely Child', 'Bouchara', and the operas 'Kopernikus' and 'Marco Polo'. He went to Paris in 1982 to work on a new opera, the composition of which was interrupted by his murder. On his desk was the manuscript of his last work, uncannily entitled "Do You Believe in the Immortality of the Soul?" Vivier's is a tragic but life-affirming story, intimately connected to his passionate music. Bob Gilmore is a musicologist and performer and teaches at Brunel University in London. He is the author of 'Harry Partch: A Biography'.

Le Lunatique, « Le temps du changement » : Intimidation, ostracisme et homophobie dans le milieu hip-hop au Québec - Lamort, Kapois (Les boss du Québec. R.A.P. du fleur de lysée. Analyse socio-historique et sociologique du hip-hop dans la société québécoise, 2014)
Le tout premier livre monographique et scientifique axé sur la culture Hip-Hop au Québec, rédigé par Kapois Lamort, historien spécialiste diplômé de l’Université du Québec à Montréal ( UQAM); cet ouvrage retrace les 35 ans d’existence du H.I.P.H.O.P. à travers la société québécoise de 1979 à 2015

Notre Clémence. D'amour et d'humour - Pedneault, Hélène (Éditions de l'Homme, 2013)
Humoriste, poète, monologuiste, comédienne: Clémence DesRochers s'est constamment réinventée au cours de sa prolifique carrière. Prenant la parole au nom des gens d'ici, elle a tour à tour exprimé avec justesse les joies et les peines des ouvriers, des femmes, des laissés-pour-compte et des homosexuels. Chaque fois, ses mots nous ont touchés droit au cœur, nous faisant à la fois sourire et réfléchir. Ce livre rend hommage au parcours exceptionnel d'une auteure profondément humaine, accessible et chaleureuse qu'un prénom suffit à désigner. Redécouvrez Clémence, la femme, l'artiste, la peintre du quotidien qui n'a jamais cessé d'esquisser notre portrait.

"The Cult of the Diva" – Rufus Wainwright as Opera Queen - Smith, Oliver C. E. (Transposition. Musique et Sciences Sociales, 2013)
The music of Rufus Wainwright has been afforded much critical acclaim thanks to the singer-songwriter’s understanding of Queer cultural history, and the candor with which he explores (homo)sexuality in his music. This case study seeks to examine his use of opera in particular, and how Wainwright uses the historical trope of the opera queen to incorporate his own queerness into music, thus asserting an authority of difference and challenging the dominant (hetero)norm constructions of masculinity in popular music. Wainwright disregards any cultural framework imposed by heternormativism, and reclaims the Orphic figure of operatic authority as one of queer power through this absence. By drawing on his own relationship with opera, Wainwright exploits the right this gives him by reinterpreting cultural history, and revising the pejorative stereotype that is an opera queen.
Keywords: Eurydice; Hallelujah; Jeff Buckley; Memphis Skyline; Rufus Wainwright; Waiting For A Dream; Want Two; diva; gay; heteronormativism; identity; masculinity; opera; queer; stereotype

De l’ombre à la lumière : fragments pour une analyse des trois premiers albums d’Ariane Moffatt - Doyon, Noémie (Canadian Folk Music, 2012)

Femme-acrobate, femme-automate : Le Fil de Camille et Le Cœur dans la tête d'Ariane Moffatt - Doyon, Noémie (Chanson et performance. Mise en scène du corps dans la chanson française et francophone, 2012)
La moustache de Brassens, la robe noire d'Edith Piaf, les paillettes de Claude François, les cheveux de Dalida ... Les chanteurs ont un corps indissociable de leurs chansons. Ce livre s'intéresse à la présence physique de la musique populaire, à sa performance sur scène et sur le disque. Voici observées les tensions sociales, sexuelles et identitaires qui sous-tendent la performance musicale

Le pouvoir créateur d’Alfred et de Clémence - Roy, Julie; Fortier, Hélène (Revue de Bibliothèque et Archives nationales du Québec, 2012)

Entre stabilité et mouvement : l'oscillation spatiale dans le diptyque "Want" de Rufus Wainwright - Mathieu-Lessard, Jeanne (Université Laval, 2011)
Ce mémoire propose l’analyse de chansons extraites du diptyque Want (formé des albums Want One et Want Two), de l’auteur-compositeur-interprète Rufus Wainwright, en regard des relations entre l’énonciateur et l’espace. La notion d’oscillation spatiale, définie en introduction, est au cœur de la situation de l’énonciateur et se déploie sous de multiples formes dans les cinq chansons à l’étude. « Oh What a World » et « I Don’t Know What It Is » sur Want One, « Hometown Waltz », « Memphis Skyline » et « Old Whore’s Diet » sur Want Two, ont été choisies pour la façon dont la relation à l’espace y agit de même que pour leur emplacement dans l’ensemble. La position de l’énonciateur mise en évidence dans chaque analyse s’inscrit au sein d’un parcours, que l’étude préliminaire du paratexte des albums aura d’ailleurs mis en évidence.

Performing ‘Judy’: The Creation and Function of Cover Personae in Popular Music in Rufus Wainwright's Judy Garland Concerts - O'Connell, Sam (Contemporary Theatre Review, 2011)

One Day in the Life of Rufus Wainwright - Hailand, Tim (Hailand Books, 2010)
One Day in the Life of Rufus Wainwright follows the singer-songwriter from New York City to Boston for his performance at the Boston Opera House, which featured his sister Martha Wainwright as a special guest. With an intro by NYC nightlife legend Cherry Vanilla and text from Rufus himself.

There Will Be Rainbows: A Biography of Rufus Wainwright - Lake, Kirk (Itbooks, 2010)
"No contemporary pop performer's work mixes innovation and tradition like Rufus Wainwright's. He is the son of singer, songwriter, actor Loudon Wainwright III and legendary Canadian folk singer Kate McGarrigle whose story is one of towering highs and rock bottom lows in which family influences, sexual experimentation, and a crystal meth addiction in the early 2000s have greatly contributed."

The Montreal Sailors' Institute and the Homosexual Sailor: A Model for Moral Reform in the Nineteenth and Twentieth Centuries - Renwick, Claire (Montreal as Palimpsest, 2010)

“Oh What a World”: Queer Masculinities, the Musical Construction of a Reparative Cultural Historiography, and the Music of Rufus Wainwright - Schwandt, Kevin C. (Université du Minnesota, 2010)
Throughout his ascendancy in fame and cultural visibility, singer/songwriter and gay pop icon Rufus Wainwright's output has been consistently related, by scholars and critics alike, to camp aesthetics, modes of artistic expression typically understood as emerging from queer communities, particularly certain gay male populations, but ones whose political potential is highly contested. Traditional conceptions of camp, as most famously articulated by Susan Sontag in the 1960s, emphasize style over content, necessarily rendering it politically-disengaged. However, scholars have vehemently challenged conceptions like Sontag's, in order to reclaim camp as a potent means to facilitate queer world-making and a powerful resistance to heteronormativity. I examine Wainwright's image and music in order to theorize a new queer interpretive listening position. Specifically, I draw upon the literary perspective of “reparative reading,” articulated by Eve Kosofsky Sedgwick in opposition to what she describes as “paranoid reading,” to propose a uniquely queer approach to musical and cultural historiography, exemplified by Wainwright's music. Much of the current queer musicology focuses on lost histories, systematic marginalization, and the commoditization of queer identities. While such approaches have produced important insights, thorough examination of the relationships between queer cultural products and their queer reception has proven elusive. This project suggests a unique approach to understanding the musical construction of a specific kind of queer masculinity, one which combines authorial creation with reparative conceptions of reception, in order to theorize a uniquely gay male interpretive position. When viewed through a theoretical lens combining politically-potent conceptions of camp performativity with a reparative reading position, Wainwright's music strikingly enacts Philip Brett's call to claim, not historical evidence, but the right of interpretation, emerging as an act of resistance via the reclamation and consolidation of a queer interpretive authority. In this way, Wainwright articulates both a rupture in the history of queer masculinity and a powerful means of resistance to the often-exclusionary relationships between literary, musical, and artistic objects and the heteronormative cultural systems in which they are created.
Keywords: Communication and the arts; Gay history; Gay rights; Historiography; Masculinities; Popular culture; Queer; Reparative reading; Rufus; Social sciences; Wainwright

All these poses, such beautiful Poses: articulations of queer masculinity in the music of Rufus Wainwright - Jones, Matthew J. (Université de Géorgie, 2008)
Singer-composer Rufus Wainwright uses specific musical gestures to reference historical archetypes of urban, gay masculinity on his 2002 album Poses. The cumulative result of his penchant for pastiche, eschewal of traditional musical boundaries, and self-described hedonism, Poses represents Wainwright’s direct engagement with the politics of identity and challenges dominant constructions of (homo)sexuality and masculinity in popular music. Drawing from a vast lexicon of musical styles, he assembles an idiosyncratic persona, ignoring several decades of pop with an “utter lack of machismo [and] a freedom that comes to outsiders disinterested in meeting the requirements of the dreary status quo.”1 Though analysis of musical and lyrical characteristics of Poses, I establish a dialectic between Wainwright’s musical persona and four historical modes of urban gay masculinity: the 19th Century English Dandy, the French flaneur, the 20th Century gay bohemian, and the “Clone.” In doing so, I introduce Wainwright as a reinvigorating force, resuscitating the subversive potential of radical gay sexuality as a 21st Century model for imagining gay male subjectivity.

Sobre meninos e homens Por uma leitura edipiana: Rufus Wainwright e a canção Dinner at Eight [Des garçons et des hommes: Rufus Wainwright et la chanson "Dinner at Eight"] - Júnio, José Mariano Tavares (Cadernos do LINCC, 2008)
O artigo reflete sobre a obra do compositor novaiorquino Rufus Wainwright iconsiderando as suas influências no sentido de explicar, ao menos em parte, a originalidade melódica e harmônica presente na arquitetura de suas canções, a grandiloqüência dramática dos arranjos, e a complexidade de sua persona artística, opondo, a uma forte teatralidade camp, a melancolia trágica, cortante, do solitário e outsider.

L'identité culturelle dans « Montréal », d'Ariane Moffatt : une analyse musicale sémiologique - Laurier-Cromp, Mélanie (Université McGill, 2008)
La chanson « Montréal », d'Ariane Moffatt, a remporté un vif succès durant l'été 2006. Ce mémoire examine les causes de cette popularité. Après une revue des diverses méthodes existantes en recherche en musique populaire, trois types d'analyse se succèdent. En premier lieu, l'étude présentée ici décrit la chanson de manière théorique; on y observe le fonctionnement de la voix, de la mélodie, de la métrique, de la basse, des phrases, de la tonalité, des accords et des instruments utilises, images par une transcription précise de l'enregistrement de la chanson. Puis, le présent travail étudie les codes musicaux qui se retrouvent dans «Montréal». Dans cette deuxième section, le message musical du morceau est analysé, en tenant compte du contexte socioculturel de l'été 2006, de l'histoire nationale et musicale qui a précédé la sortie de cette pièce et des paroles de la chanson. Finalement, cette étude investigue la composante identitaire de «Montréal» en examinant les croyances nationalistes des Québécois, la place de la chanson dans l'imaginaire collectif de ce peuple, et la tradition musicale populaire de la province.

Listening to/at/with Marilyn Lerner’s "They’re All in Families" - McNeilly, Kevin (Critical Studies in Improvisation / Études critiques en improvisation, 2008)
Marilyn Lerner’s audio-art composition “They’re All in Families” (1998) re-works a sound clip from a virulently homophobic message left on an answering machine, turning hate-speech back on itself to expose the rhythms and textures of verbal violence.

Rufus Wainwright [entrevista]: Geni i figura - Broc, David (Benzina: Revista d'excepcions culturals, 2007)

Keeping Time with Lesbians on Ecstasy - Halberstam, J[ack] (Women and Music: A Journal of Gender and Culture, 2007)

A Queer Protocol of Homage: Chambres de Ténèbres/Tombeau de Claude Vivier By Marko Nikodijević - Novak, Jelena (International Journal of Music New Sound, 2007)
The music of Canadian composer Claude Vivier (1948-1983) was used as a fractalized material for the creation of the composition Chambres de ténèbres/tombeau de Claude Vivier (2005) by Marko Nikodijević. Vivier’s opus and his marginal queer acting were the pillars of Nikodijević’s meticulous reading/deconstructing of Vivier’s world through his own artistic dilemmas.

Rufus Wainwright. Interview by Paul Zollo - Zollo, Paul (Song: the World’s Best Songwriters on Creating the Music that Moves Us, 2007)
Song is an enthralling compilation of songwriting wisdom from 100 of the biggest names in music. From country to rock to folk to alternative, this genre-spanning collection of interviews captures the anecdotes, history, and wisdom of the best songwriters around - in their words. An entertaining read as well as an indispensable guide to the art and craft of songwriting, Song is a must-have resource for the aspiring, amateur, or professional musician. Inside, you'll find entertaining and enlightening interviews from great songwriters such as Smokey Robinson, Willie Nelson, Jewel, Kenny Chesney, Cat Stevens, Jack Johnson, Sheryl Crow, John Legend, John Mellencamp, Ray Charles, Clint Black, Rob Thomas, Dolly Parton, Rufus Wainwright, Bob McDill, Lyle Lovett, Keith Urban, Beck, M. Ward, Lou Reed, Roger Miller, Grant-Lee Phillips, and John Denver.

Rufus Wainwright - De Curtis, Anthony (In Other Words: Artists Talk About Life and Work, 2005)

Radical Queers: A Pop Culture Assessment of Montréal's Anti-Capitalist Ass Pirates, the Panthères roses, and Lesbians on Ecstasy - Hogan, Mélanie (Canadian Woman Studies, 2005)
Cet article nous explique comment des artistes montréalaises queer radicales, Anti-Capitalists Ass Pirates, les Panthères roses et Lesbians on Ecstasy, ont transformé la sphère publique en intégrant politique et célébrations dans leurs importants messages à la population.

La singulière pluralité de Marilyn Lerner - Denis, Dominique (Liaison, 2004)

When Shirley Met Florence - Bezalel, Ronit (Office national du film du Canada, 1994)
Portrait intime de deux femmes juives au milieu de la soixantaine, l'une homosexuelle et l'autre hétérosexuelle, dont l'amour l'une pour l'autre et la musique qu'elles créent ensemble transcendent les différences. L'attachement de Florence pour Shirley défie toute catégorisation.

Aimer Clémence ou se voir différent - D'Amours, Réal (La chanson en question(s), 1986)

Clémence Desrochers : humour et solitude - Lacoursière, Yvan (Université du Québec à Trois-Rivières, 1981)

Michel Louvain. Phénomène ou artiste préfabriqué - Lusignan, Francine (Éditions Mont D'Or, 1962)